Determining the shape of a human vocal tract from pressure measurements at the lips. (3rd October 2017) - Aktosun, Tuncay; Machuca, Alicia; Sacks, Paul
Abstract: The inverse problem of determining the cross-sectional area of a human vocal tract during the utterance of a vowel is considered in terms of the data consisting of the absolute value of sound pressure at the lips. If the upper lip is curved downward during the utterance, it is shown that there may be up to an M -fold nonuniqueness in the determination, where M is the maximal number of eligible resonances associated with a related Schrödinger operator. Each of the M such distinct candidates for the vocal-tract area corresponding to the same absolute pressure is uniquely determined. The mathematical theory is presented for the recovery of each candidate for the vocal-tract area, and the admissibility criterion for each of the M candidates to be a vocal-tract radius is specified. On the other hand, if the upper lip is horizontal or curved upward during the utterance, then the inverse problem has a unique solution. The theory developed is illustrated with some examples.